INVESTMENT DECISION ANALYSIS: ASSESSMENT OF INVESTMENT RISK CRITERIA AND MEASUREMENT - Ni Komang Septia Noriska; Sri Hartati; Fahmi Damarjati Ruseka (Adisam Publisher, 2024)
Criteria assessment and risk measurement are key elements in an effective investment decision-making process. These two aspects complement each other and provide a strong foundation for making rational, balanced investment decisions that are in line with the company's strategic objectives. Investment criteria assessment includes factors such as potential returns, liquidity, duration, and alignment with the company's strategic objectives. Criteria assessment provides a strong basis for evaluating the feasibility of an investment, while risk measurement ensures that the risks taken can be managed in accordance with the company's risk tolerance. The combination of these two approaches allows companies to make more rational, balanced investment decisions that support sustainable growth. Effective implementation of criteria assessment and risk measurement has a positive impact on financial performance, increasing return on investment, maintaining financial stability, and strengthening stakeholder trust. This study contributes to a deeper understanding of the importance of criteria assessment and risk measurement in investment decision-making, as well as providing practical guidance for companies in improving the quality of their investment decisions amidst the ever-evolving market dynamics.